Comparative Genomic Analysis and Characterization of Two Salmonella enterica Serovar Enteritidis Isolates From Poultry With Notably Different Survival Abilities in Egg Whites - Wang, Yanyan; Jia, Ben; Xu, Xuebin; Zhang, Lida; Wei, Chaochun; Ou, Hongyu; Cui, Yan; Shi, Chunlei; Shi, Xianming (Frontiers in Microbiology, 2018)
Salmonella enterica serovar Enteritidis (Salmonella Enteritidis) is a globally important foodborne pathogen, and the contaminated chicken eggs are the major source of salmonellosis in humans. Salmonella Enteritidis strains are differentially susceptible to the hostile environment of egg whites. Strains with superior survival ability in egg whites are more likely to contaminate eggs and consequently infect humans. However, the genetic basis for this phenotype is unclear. We characterized two Salmonella Enteritidis strains isolated from chicken meat that had similar genetic backgrounds but large differences in survival ability in egg whites. Although genome comparisons indicated that the gene content and genomic synteny were highly conserved, variations including six insertions or deletions (INDELs) and 70 single nucleotide polymorphisms (SNPs) were observed between the two genomes. Of these, 38 variations including four INDELs and 34 non-synonymous SNPs (nsSNP) were annotated to result in amino acid substitutions or INDELs in coding proteins. These variations were located in 38 genes involved in lysozyme inhibition, vitamin biosynthesis, cell division and DNA damage response, osmotic and oxidative protection, iron-related functions, cell envelope maintenance, amino acid and carbohydrate metabolism, antimicrobial resistance and type III secretion system. We carried out allelic replacements for two nsSNPs in bioC (biotin synthesis) and pliC (lysozyme inhibition), and two INDELs in ftsK and yqiJ (DNA damage response) by homologous recombination, and these replacements did not alter the bacterial survival ability in egg whites. However, the bacterial survival ability in egg whites was reduced when deletion mutation of the genes bioC and pliC occurred. This study provides initial correlations between observed genotypes and phenotypes and serves as an important caveat for further functional studies.